Teachers’ and students’ perception toward the use of Google Form as English Language Test Media in SMAN 5 SIDRAP - Nurfadillah Nurfadillah; Zulfah Fakhruddin; Maghdahalena Tjalla; Abdul Haris Sunubi; Arqam Arqam (Universitas Muhammadiyah Enrekang, 2022)
This research aimed to find out teachers’ and students’ perceptions toward using Google form as test media in SMAN 5 SIDRAP. This research used descriptive quantitative, the researcher collected the data by using a questionnaire, the total sample was 3 English teachers and 133 students of SMAN 5 SIDRAP, determined by using purposive sampling. The results showed that (1) Overall the results of the teacher's response showed that 87% of the teacher's responses were in the easy category. On the preparation, implementation, and evaluation indicators, all items fall into the easy and neutral category. Most teachers have a positive perception of the use of the Google form as an English language test media. (2) The results of the overall student responses to the 15 items show that 71% of student responses are in the easy category. In the preparation, implementation, and evaluation indicators, most students positively respond to the use of Google form as an English language test media.